The Heterogeneous Effects of Family Structure on Early Child Health (Epidemiology, Biostatistics, and Public Health, 2022)
BackgroundEnding preventable deaths of newborns and children under 5 years of age by 2030 is one of the targets of the Sustainable Development Goals. Data from the 2013-14 Zambia Demographic and Health Survey shows that there has been improvements in some indicators of child health over the years and this has coincided with the widespread demographic changes in family formation. It’s hypothesized that children from monogamous households tend to have much better health outcomes compared to single or polygynous households. This study therefore set out to examine the effect of heterogeneous family structures on early child health.MethodsUsing data from the 2013-14 ZDHS, the study employed the Kids Recode (KR) data file which contains information about children under the age of five (5) of interviewed women. The analysis was conducted at three levels: descriptive, bivariate and multivariate. ResultsThe study established that family structure had a statistically significant effect on early child health and that there was heterogeneity in the health outcomes of the children from different forms of marriage, with the ever married and polygamous marriage categories showing higher odds of having underweight children. The study also established that mother’s nutrition status, region, sex of child, mother’s age at birth of the child and child vaccination were also among other factors associated with the early child health in Zambia. ConclusionThere is need for the government to implement policies that will limit the exposure of children to adverse health which would require more costly interventions later in life.